2003
DOI: 10.3758/bf03196442
|View full text |Cite
|
Sign up to set email alerts
|

Experimental manipulations of the phenomenology of memory

Abstract: We investigated the effects of visual input at encoding and retrieval on the phenomenology of memory. In Experiment 1, participants took part in events with and without wearing blindfolds, and later were shown a video of the events. Blindfolding, as well as later viewing of the video, both tended to decrease recollection. In Experiment 2, participants were played videos, with and without the visual component, of events involving other people. Events listened to without visual input were recalled with less reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 30 publications
3
46
0
1
Order By: Relevance
“…Greenberg and Rubin (2003) interpreted these findings by proposing that impairment of visual memory disrupts the entire retrieval process because AM retrieval depends upon the interconnection and activation of many separate systems (also see Rubin, 2007b). Consistent with these findings, Rubin, Burt, and Fifield (2003) showed that degrading visual input in healthy individuals during the encoding of staged laboratory events, by asking participants to wear blindfolds, impaired some phenomenological aspects of later memory recall.…”
Section: Vividnesssupporting
confidence: 57%
See 2 more Smart Citations
“…Greenberg and Rubin (2003) interpreted these findings by proposing that impairment of visual memory disrupts the entire retrieval process because AM retrieval depends upon the interconnection and activation of many separate systems (also see Rubin, 2007b). Consistent with these findings, Rubin, Burt, and Fifield (2003) showed that degrading visual input in healthy individuals during the encoding of staged laboratory events, by asking participants to wear blindfolds, impaired some phenomenological aspects of later memory recall.…”
Section: Vividnesssupporting
confidence: 57%
“…First, the reliving scale could be considered a better subjective measure of recollection in AM than remember/know because it does not require the assumption of a dual-process model (Wixted, 2007;Yonelinas, 2002). Second, reliving is a better predictor of recollection in AMs compared to the remember/know scale, which is a better predictor of confidence in AMs (Rubin, Burt, et al, 2003;Rubin, Schrauf, & Greenberg, 2004). In the SPO condition participants were asked to indicate the amount of understanding of the other person's perspective.…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…These questions were taken from the Autobiographical Memory Questionnaire (AMQ), which was derived from various existing autobiographical and general memory theories and is sensitive to the conscious experience of remembering (Rubin, Burt, & Fifield, 2003;Rubin, Schrauf, & Greenberg, 2003;Sheen et al, 2001). This allows us to study not just global variations due to emotion, but also differential effects on specific properties of autobiographical memory.…”
Section: Experiments 1 Methodsmentioning
confidence: 99%
“…To check the correlational findings involving vividness of visual memory and recollection, we had people take part in two half-hour events (Rubin, Burt, & Fifield, 2003). In each event, half the participants were blindfolded and half were not.…”
Section: Phenomenologymentioning
confidence: 99%